Kurdish vowels - Bahdinan region acoustic research - Bijankhan, Mahmood; Saleh, Salwa F. (Humanities Journal of University of Zakho, 2017)
In general, every language is composed of some (vowel and consonant) sounds, the numbers of these sounds are different for each language. Surely vowel sounds play an important role in phonetic system of every language. Mostly each language has its special vowels which are different in number. In Kurdish language as other languages we have a number of vowels, but till now, there is argue about their exact number, Kurdish and foreign researchers have different opinions about it. This research under the title (Kurdish vowels - Bahdinan region acoustic research) has tried to analyze Kurdish vowels in a sound laboratory and under an acoustic environment, and this is for having more scientific results. The main hypothesis of this research is (we can use a laboratory environment by the help of F1 means: Formant 1, F2 means: Formant 2 and duration means: the duration which needs to express the vowel, to determine Kurdish vowels - Bahdinan region and differentiate them. At the end the researcher has proved that there are 8 vowels in Kurdish language - Bahdinan region.